2021
DOI: 10.1177/03611981211007481
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection and Classification of Pavement Distresses using 3D Pavement Surface Images and Deep Learning

Abstract: Pavement distresses lead to pavement deterioration and failure. Accurate identification and classification of distresses helps agencies evaluate the condition of their pavement infrastructure and assists in decision-making processes on pavement maintenance and rehabilitation. The state of the art is automated pavement distress detection using vision-based methods. This study implements two deep learning techniques, Faster Region-based Convolutional Neural Networks (R-CNN) and You Only Look Once (YOLO) v3, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In [15] (2021), two deep learning techniques were implemented for automated pavement distress detection and classification, namely Faster Region-based Convolutional Neural Networks (R-CNN) and YOLOv3. These deep learning frameworks were trained on a dataset the authors collected and validation accuracy was indicated using Average Precision (AP) and Receiver Operating Characteristic (ROC) curves.…”
Section: Machine and Deep Learning Approaches For Manhole Detection I...mentioning
confidence: 99%
“…In [15] (2021), two deep learning techniques were implemented for automated pavement distress detection and classification, namely Faster Region-based Convolutional Neural Networks (R-CNN) and YOLOv3. These deep learning frameworks were trained on a dataset the authors collected and validation accuracy was indicated using Average Precision (AP) and Receiver Operating Characteristic (ROC) curves.…”
Section: Machine and Deep Learning Approaches For Manhole Detection I...mentioning
confidence: 99%
“…The development of vision-based automated pavement distress identification methods is well documented in the literature. Methods like image processing (intensitythresholding, edge detection, and seed-based) and machine learning (unsupervised learning, supervised learning, and DL) have been widely used for distress identification and quantification (12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Application Of Vision-based DL Models In Pavement Distress M...mentioning
confidence: 99%
“…e 3D laser imaging technology has been used to evaluate crack [66,67], pothole [68], raveling [69], rutting [70], joint [71], and texture [72]. Ghosh et al [73] employed YOLO and Faster R-CNN to detect cracks in range images collected by the 3D imaging system. Yang et al [74] utilized 3D laser technology to measure the growth of crack lengths when they are sealed and non-sealed to quantify the crack sealing benefit.…”
Section: D Image Data In Pavementmentioning
confidence: 99%